Frequent amplification of HDAC genes and efficacy of HDAC inhibitor chidamide and PD-1 blockade combination in soft tissue sarcoma. Issue 2 (26th February 2021) - Que, Yi; Zhang, Xiao-Long; Liu, Ze-Xian; Zhao, Jing-Jing; Pan, Qiu-Zhong; Wen, Xi-Zhi; Xiao, Wei; Xu, Bu-Shu; Hong, Dong-Chun; Guo, Tian-Hui; Shen, Lu-Jun; Fan, Wei-Jun; et al.
Abstract : Background: The advent of immune checkpoint therapy has been a tremendous advance in cancer treatment. However, the responses are still insufficient in patients with soft tissue sarcoma (STS). We aimed to identify rational combinations to increase the response to immune checkpoint therapy and improve survival. Methods: Whole-exome sequencing (WES) was performed in 11 patients with liposarcoma. Somatic copy number alterations (SCNAs) were analyzed at the gene level to identify obvious amplification patterns in drug-target genes. The expression and prognostic value of class I histone deacetylases (HDACs) was evaluated in 49 patients with sarcoma in our center and confirmed in 263 sarcoma samples from The Tumor Cancer Genome Atlas (TCGA) database. Q-PCR, flow cytometry and RNA-seq were performed to determine the correlations between class I HDACs, chidamide and PD-L1 in vitro and in vivo. The efficacy of combining chidamide with PD-1 blockade was explored in an immunocompetent murine model and a small cohort of patients with advanced sarcoma. Western blot, ChIP assay and dual luciferase assessment were applied in the mechanistic study. Results: The HDAC gene family was frequently amplified in STS. SCNAs in the HDAC gene family were extensively amplified in 8 of 11 (73%) patients with liposarcoma, based on a drug-target gene set, and we verified amplification in 76.65% (197/257) of cases by analyzing TCGA sarcoma cohort. Class I HDAC expression is associated with a poor prognosis for patients with STS, and its inhibition is responsible for promoting apoptosis and upregulating of programmed cell death ligand 1 (PD-L1). The HDAC class I inhibitor chidamide significantly increases PD-L1 expression, increased the infiltration of CD8 + T cells and reduced the number of MDSCs in the tumor microenvironment. The combination of chidamide with an anti-PD-1 antibody significantly promotes tumor regression and improves survival in a murine model. Moreover, chidamide combined with the anti-PD-1 antibody toripalimab is effective in patients with advanced and metastatic sarcoma, and the side effects are tolerable. Mechanistically, chidamide increases histone acetylation at the PD-L1 gene through the activation of the transcriptional factor STAT1. Conclusions: The combination of chidamide and anti-programmed cell death 1 (PD-1) therapy represents a potentially important strategy for STS.